Investigation and analysis of the transmission of evil in Persian mystical texts - Afrooz Khodabadehloo; Seyyed Mohsen Hosseini Moakhkhar; Seyyed Ali Ghasemzadeh (ادبیات عرفانی)
Dignity is a significant theme in Sufi texts. One of the types of dignity based on the possession of souls is the transmission of evil, which is the exact opposite of healing. This article aims to investigate the issue of the transmission of evil, including its motivations and types as depicted in mystical stories derived from the most important mystical texts. The investigation employs library studies and descriptive-analytical methods, and of course, matching with myths. Based on the findings of the research, in such anecdotes, the owner of dignity causes evil (death or illness) to a healthy person with different purposes and intentions through spiritual power. The motivations and purposes of the transmission of evil are to heal the sheikh's heart, to prove the sheikh's spiritual power, to make the disciples obedient, to ward off evil and oppression from the people, to punish and guide the unbelievers, to defend oneself (in a situation of guilt or an unfavorable situation) and to destroy. In addition to motives, the transmission of evil can be classified from two perspectives: first, from the point of view of being permanent (death) or temporary (disease), and second, from the direct (conscious) and indirect (unconscious) direction of the transfer of evil.